STABILITY INDICATING RP-HPLC METHOD FOR ESTIMATION OF REPAGLINIDE IN RABBIT PLASMA - NAVAMANISUBRAMANIAN, RAJA; PANCHAGIRI, SABITHA; NERELLA, RAGHUNANDAN; DURAIPANDIAN, CHAMUNDEESWARI; SEETHARAMAN, SHANMUGANATHAN (International Journal of Applied Pharmaceutics, 2019)
Objective: A simple, selective and sensitive reverse-phase high-performance liquid chromatography (RP-HPLC) method to estimate repaglinide (REP) in rabbit plasma using rabeprazole (RAB) as an internal standard was developed and validated for various qualifications. Methods: The chromatographic separation was performed on C18 (2) analytical column (5 μ, 250×4.6 mm) using acetonitrile: 0.05% trifluoroacetic acid in water (55:45, v/v) as mobile phase at the flow rate of 1 ml/min. Validation of the analytical method was performed as per ICH guidelines. Results: The retention times of REP and RAB were found at ~4.3 and 5.1 min respectively, with adequate system suitability parameters (theoretical plates ≥3619, tailing factor ≤1.38, resolution factor 2.37). The method has linearity over a concentration range of 10 to 1000 ng/ml (r2=0.9987). The results of accuracy (≥98.17%), intra-, inter-day precision (≤2.9%), recovery (101.21±2.09%) and process efficiency (99.77±3.74%) found satisfactory with no matrix effect. The analyte in samples were found stable up to 6 h, 3 freeze-thaw cycles and not more than 2 mo corresponding to bench-top, short and long term stability studies respectively. Conclusion: The developed RP-HPLC method for estimation of REP in rabbit plasma was developed. The method was found to be rapid, cost-effective and accurate to estimate the REP from the sample matrix. The method can be a most useful tool for in vivo study of REP in the rabbit.